2016
DOI: 10.1111/ijfs.13157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined microwave‐hot air drying and superheated steam drying on physical and chemical properties of rice

Abstract: Summary Jasmine rice (Oryza sativa L.) was subjected to two drying operations: combined microwave‐hot air drying (MHA) at initial power intensity of 3, 4 and 6 W g−1 and superheated steam drying (SHS) at 300 °C and 400 °C. During drying, kinetic rate constants of SHS were significantly higher than those of MHA. Both drying operations could decrease enthalpy of starch gelatinisation from 9.28 J g−1 to 1.64–6.17 J g−1, increase gelatinisation extent to 33.51–82.33%, decrease crystallinity from 28.87% to 18.15–21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…They concluded that the A‐type crystallinity decreases with an increase in drying air temperature. Horrungsiwat et al () studied the drying of rice with superheated steam and microwave hot air and reported A‐type crystallinity at 2θ of 15°, 17°, 18°, and 23°.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They concluded that the A‐type crystallinity decreases with an increase in drying air temperature. Horrungsiwat et al () studied the drying of rice with superheated steam and microwave hot air and reported A‐type crystallinity at 2θ of 15°, 17°, 18°, and 23°.…”
Section: Resultsmentioning
confidence: 99%
“…Taechapairoj, Prachayawarakorn, and Soponronnarit () dried paddy using superheated steam in a fluidized bed dryer at a temperature in the range 150–170 °C and reported gelatinized and swelled structure of starch granules. Horrungsiwat et al () studied the microstructure of rice dried by microwave and superheated steam and reported a change in starch structure from rough to smooth due to partial gelatinization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to several studies, rice starch was classified into A‐type. However, the formation of amylose complex could change the crystalline pattern of starch into V‐type after some treatments such as soaking (Manful, Grimm, Gayin, & Coker, ), drying (Horrungsiwat, Therdthai, & Ratphitagsanti, ), and parboiling (Derycke et al, ), leading to change in starch properties. Thermal properties have been investigated using differential scanning calorimetry (DSC) to determine the gelatinization of rice after treatment which may be related to cooking properties and glycemic response of brown rice (Ramírez‐Miranda et al, ; Zhu, Liu, Wilson, Gu, & Shi, ).…”
Section: Introductionmentioning
confidence: 99%